Preserving and Promoting Health among Middle-aged Women: A Grounded Theory Study - nasrin rezaee; Naimeh Seyedfatemi; Mahvash Salsali (Kerman University of Medical Sciences, 2020)
Introduction: Middle age is a developmental stage. Women in this stage are capable of preserving and promoting their own health as well as the health of other members of their families. In fact, women's health can assure other family members' health. Studies indicated that to preserve and promote their own health, women take several initiatives, which are process-based. Accordingly, the present study aims to identify the processes used for preserving and promoting health process in middle-aged women. Methods: This qualitative study was carried out using a grounded theory method. The participants were 20 middle-aged women who were selected by purposive and theoretical sampling. The required data were collected by semi-structured interviews with the participants. Data collection and analysis were done simultaneously from the first stage. Accordingly, all the recorded interviews were transcribed. Then, the transcribed data were analyzed using Strauss and Corbin's approach and the extracted concepts and themes were categorized. Results: Changes in physical and mental health status are identified as a main concern of middle-aged women. The ongoing process to remove concerns and preserve and promote health among the participating women appeared in maintaining im/balance in health, in/efficient adjustment, and moving toward change. Conclusion: The health-oriented behaviors were represented by three forms of process. In fact, these three formations are not independent of each other, but, paralleled, interrelated and with different speeds reinforced health-oriented behaviors among women to preserve and promote their health. The identification of health-oriented behaviors formation in middle-aged women can help community health nurses know the type of behaviors, processes, and elements that enable women to preserve and promote their own health.